Principles matter the Constitution, progressives, and the Trump Era - Ball, Carlos A. (Oxford University Press, 2021)
Progressives who opposed the Trump administration's policies found themselves repeatedly relying on constitutional principles grounded in federalism, separation of powers, and free speech to resist the federal government. Although many progressives had either criticized or underemphasized those principles before Trump, the principles became vital to progressive causes after Trump was elected. Using dozens of examples from the ways in which Trump abused presidential powers, this book explains how the three sets of principles can help mitigate the harms that autocratic leaders in the Trump mold can inflict on both democratic institutions and vulnerable minorities. In doing so, the book urges progressives to follow this rule of thumb in the post-Trump era: If a constitutional principle was worth deploying to resist Trump's harmful policies and autocratic governance, then it is worth defending in the post-Trump era even if it makes the short-term attainment of progressive objectives more difficult. This type of principled constitutionalism is essential not only because being principled is good in and of itself, but also because being principled in matters related to federalism, separation of powers, and free speech will help both advance progressive causes over the long run and reduce the threats posed by future autocratic leaders in the Trump mold to our system of self-governance, to our democratic values, and to traditionally subordinated minorities. Going forward, progressives should promote and defend constitutional principles grounded in federalism, separation of powers, and free speech regardless of whether they have an ally or an opponent in the White House"--